What can the Latin American cities of Cali, Quito and Medellín learn from each other’s efforts to build sustainable food systems? - Rankin, Sara; Bonilla Findji, Osana (CGIAR Research Program on Water, Land and Ecosystems, 2019)
• Movements to create sustainable food systems in Latin America are beginning to transform agri-food dynamics and the concept of conventional urban development. • Addressing the problems associated with ensuring food and nutritional security in urban areas requires a systemic approach, collective action and the involvement of different actors and sectors. • Regional exchanges allow learning about experiences adapted to the realities of each territory, identifying successful practices, generating cooperation linkages as well as inspiring and encouraging innovation.